Miss Hudson’s Maths
Graphing When we see the rule y = 2 x + 3 we know that a line can be drawn using it. But what if we are not given a table with our coordinates for our points?? What we can do is substitute values into out rule to give us those points. Miss Hudson’s Maths
Substitution xy We can now draw our line y = 2 x + 3 y = 2 x y = 5 y = 2 x + 3 y = 2 x y = 7 y = 2 x + 3 y = 2 x y = 9 y = 2 x + 3 y = 2 x y = Miss Hudson’s Maths
y= 2 x + 3 Miss Hudson’s Maths
Changing the Rule What happens when we change the rule slightly?? The new rule is y = 2 x - 3 xy y = 2 x – 3 y = 2 x 1 – 3 y= -1 y = 2 x – 3 y = 2 x 3 – 3 y= 3 y = 2 x – 3 y = 2 x 4 – 3 y= 5 y = 2 x – 3 y = 2 x 2 – 3 y= Miss Hudson’s Maths
y= 2 x + 3 y= 2 x - 3 Miss Hudson’s Maths
Changing the Rule Again What happens if we change the again slight again?? Our new rule is y = -2 x - 3 xy y = -2 x – 3 y = -2 x 1 – 3 y= -5 y = -2 x – 3 y = -2 x 4 – 3 y= -11 y = -2 x – 3 y = -2 x 3 – 3 y= -9 y = -2 x – 3 y = -2 x 2 – 3 y= Miss Hudson’s Maths
y= 2 x + 3 y= 2 x - 3 y=- 2 x - 3 Miss Hudson’s Maths
Changing the Rule Again What happens when we change the rule again slightly?? The new rule is y = -2 x + 3 xy y = -2 x + 3 y = -2 x y= 1 y = -2 x + 3 y = -2 x y= -3 y = -2 x + 3 y = -2 x y= -5 y = -2 x + 3 y = -2 x y= Miss Hudson’s Maths
y= 2 x + 3 y= 2 x - 3 y= - 2 x - 3 y= - 2 x + 3 What do you notice? Miss Hudson’s Maths
The Rule We know that the general rule is: y = m x + c Where m is the constant difference And c is the starting number or when x=0 There is a much simpler way to draw the line without substituting values into the rule. Miss Hudson’s Maths
Another way we can define this rule is: m is the slope of the line and c is the y intercept The slope of the line is called the gradient The y intercept is where the line cuts the y axis Miss Hudson’s Maths
Gradient or the slope When we look at the gradient or the slope of a line we write it in the form of: rise run This will make more sense when we look at a graph. Miss Hudson’s Maths
y= 2 x Gradient: m= 2 1 y-intercept c = 3 y= 2 x + 3 Miss Hudson’s Maths
Gradient (m)= 1 1 y-intercept c = -1 y= 1 x - 1 Miss Hudson’s Maths
We are given the rule: y= 3 x + 1 c = 1 m = 3 1 Miss Hudson’s Maths